FENOMENA AUDITOR SWITCHING DI INDONESIA: ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHINYA (Studi Empiris Pada Perbankan yang Terdaftar di Bursa Efek Indonesia) - Amilin -; Nurhayati - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
This study examines the influence of fee audit, financial distress, size audit firm, quality withauditor switching. Sample in this study are banking industry listed in Indonesia stock exchange since2005-2008. The number of banking industry that were visited in this study were 15 company with 4year observation. The method of determining the sample is by using purposive sampling method,while the data processing methods used by reseacher are the logistic regression. The result showthat fee audit, financial distress, size audit firm, and quality audit no significantly influence to Auditorswitching in banking industry in Indonesia..